Productivity improvement and resource conservation in the use of African rangelands - Butterworth, M.H.; Lambourne, L.J. (Australian Academy of Science, 1986)
Looks into the nature of African rangelands, cattle & small stock production/productivity, nutrition limitations to production, improvement of rangeland and conservation of arid range land; presents data on estimated yield of cows in ILCA pastoral programmes, production characteristics of sheep and goats, chemical analysis for grasses & browse from s. Ethiopian rangelands, and yield & composition of forage available in Stylosanthes fodder bank in Kaduna during the dry season.